New I-V Characteristics Scan-Type MPPT Control Method for PV Generation System - Itako, Kazutaka (Journal of Technology Innovations in Renewable Energy, 2013)
This paper proposes the new scanning interval control method in I-V characteristics scan-type MPPT control for a PV generation system. From the experimental results, it is clarified that even if the value of L is low, the set detecting interval can be assured regardless of difference of the solar radiation intensity, and that the new MPPT control offers outstanding effectiveness in partially shaded environments.